Sistem Pakar Hukum Tajwid Pada Kitab Suci Al-Qur’An dengan Metode Forward Chaining - Marwan Hakim Marwan Hakim; Rusdan (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2020)
Al-Qur'an is the holy book of Muslims that was revealed to the Prophet Muhammad and is one of his greatest miracles. Reading the Qur'an in Tartile is the way of reading that the Prophet taught to his companions as he was taught by Jibril. In order to read the Qur'an properly, one needs to learn the science of recitation. The scholars stated that the law of studying tajwid is fardhu kifayah but practicing tajwid when reading the Al-Qur'an is fardhu ain or obligatory for men and women who are mukallaf. This expert system was built and designed to make it easier to learn tajwid so that it is not boring, so that it can be learned without having to meet face to face with the Koran teacher and can be learned anywhere and anytime.